2019
DOI: 10.1038/s41598-019-54991-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of multi-layered varnishes on moisture protection and vibrational properties of violin wood

Abstract: Violin varnishes are known to affect both moisture absorption and vibrational properties of violin wood. However, traditional multi-layered varnish systems suffer from substantial wear as a result of intensive use, which calls for deeper understanding of the specific impact of individual layers. Using sophisticated in-situ neutron imaging and vibrational modal analysis, we show how wood sorption and vibrational behavior of tonewood depend on the build-up of the varnish system. The results demonstrate the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The weights (including the aluminium tape) and their relative changes are reported in Table 2. The spatial and time-dependent moisture content (MC) distribution within the wood is obtained by neutron radiography [28,29]. The "ovendry density" of maple (used as reference for calculating MC), was determined experimentally on replicas, obtaining a value of 550.0 (±0.1) kg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weights (including the aluminium tape) and their relative changes are reported in Table 2. The spatial and time-dependent moisture content (MC) distribution within the wood is obtained by neutron radiography [28,29]. The "ovendry density" of maple (used as reference for calculating MC), was determined experimentally on replicas, obtaining a value of 550.0 (±0.1) kg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, the humidity was increased to 95% RH, allowing to investigate the individual spatial moisture content (MC) changes during the sorption process. The measurement lasted over a period of approximately 12 h, during which neutron radiography images were collected every 5 min [28,29]. The radiographic raw data were post-processed with dark-current and flat-field corrections.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the color of the finish of the violins and the quality of the surface in terms of clarity of wood structure at the time of investigations can be seen in Figure 3. Aspects related to the color tones, the type of finishes and the thickness of the penetration of the wood finish were studied by [3,11,12]. It was found that frequently used and aged instruments show a pattern of wear due to the degradation of the varnish after extensive manipulation and weighing by the violinist, which makes it difficult to analyze the structure of the wood [20][21][22].…”
Section: Studied Structuresmentioning
confidence: 99%
“…The current shape of the violin was established by Andrea Amati (1505-1578); over time, violin makers brought only small changes into the constructive elements, almost imperceptible to an ordinary visual analysis. Many of these musical instruments are rare examples of high artistic mastery and are still used as a reference in the contemporary manufacture of violins [1][2][3]. In addition to the consecrated violin makers mentioned above, violin making workshops have been developed in other regions of Europe, through violin makers who completed their apprenticeship in Italian violin makers' workshops and who imprinted the specifics of the area on their violin models.…”
Section: Introductionmentioning
confidence: 99%
“…The most charming and discussed part of a bowed stringed musical instrument is the varnish, remarkable result of the finishing treatments performed by ancient violin makers. Its role is not merely aesthetic and protective, since it influences -together with the ground coat -the mechanical and vibrational properties of the wooden parts and, consequently, the sound quality [1][2][3][4]. During the last decades, a suite of analytical techniques has been employed to investigate materials and procedures used for finishing historical string instruments [5,6], with a particular attention to those produced in Cremona (Italy) by the Amati, Guarneri, and Stradivari families [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%